Acute and chronic lung inflammation drives changes in epithelial glycans - Alvarez, Carlos A.; Qian, Emily; Glendenning, Leandre M.; Reynero, Kalob M.; Kukan, Emily N.; Cobb, Brian A. (Frontiers in Immunology, 2023)
Asthma is the most common chronic inflammatory disease and it is characterized by leukocyte infiltration and tissue remodeling, with the latter generally referring to collagen deposition and epithelial hyperplasia. Changes in hyaluronin production have also been demonstrated, while mutations in fucosyltransferases reportedly limit asthmatic inflammation. Given the importance of glycans in cellular communication and to better characterize tissue glycosylation changes associated with asthma, we performed a comparative glycan analysis of normal and inflamed lungs from a selection of murine asthma models. We found that among other changes, the most consistent was an increase in fucose-alpha1,3-N-acetylglucosamine (Fuc-alpha1,3-GlcNAc) and fucose-alpha1,2-galactose (Fuc-alpha1,2-Gal) motifs. Increases in terminal galactose and N-glycan branching were also seen in some cases, whereas no overall change in O-GalNAc glycans was observed. Increased Muc5AC was found in acute but not chronic models, and only the more human-like triple antigen model yielded increased sulfated galactose motifs. We also found that human A549 airway epithelial cells stimulated in culture showed similar increases in Fuc-alpha1,2-Gal, terminal galactose (Gal), and sulfated Gal, and this matched transcriptional upregulation of the alpha1,2-fucosyltransferase Fut2 and the alpha1,3-fucosyltransferases Fut4 and Fut7. These data suggest that airway epithelial cells directly respond to allergens by increasing glycan fucosylation, a known modification important for the recruitment of eosinophils and neutrophils.